Coronary artery bypass grafting (CABG) vs. percutaneous coronary intervention (PCI) in the treatment of multivessel coronary disease: quo vadis? —a review of the evidences on coronary artery disease - Spadaccio, Cristiano; Benedetto, Umberto (Annals of Cardiothoracic Surgery; Vol 7, No 4 (July 31, 2018): Coronary Revascularisation—Cardiology for the Surgeon, 2018)
The optimal treatment of ischemic coronary artery disease (CAD) is still controversial. A number of randomized controlled trials (RCT) and several meta-analyses have been performed and are inspiring the current guidelines. However, a univocal consensus on the optimal therapeutic strategy for multivessel disease has still not been reached yet. We reviewed the current evidence on this topic, focusing on both RCT and meta-analyses. From both short and long-term studies, it emerges that in patients with multivessel disease, coronary artery bypass grafting (CABG) is associated with better survival, lower rates of major cardiovascular events (specifically myocardial infarction or stroke) and repeat revascularization as compared with percutaneous coronary intervention (PCI) with drug-eluting stents.